“Generación de biogás en el grupo avícola San Vicente de la ciudad de Riobamba en el año 2021, a partir de las excretas de las aves de corral. Propuesta de diseño de un biodigestor”. - Fiallos Velasco, Pablo Javier (2022)
The present work constitutes a benefit to treat the organic waste generated in the San Vicente poultry group of the city of Riobamba, province of Chimborazo. For this reason, it is intended to develop a biodigester from the excreta of broiler chickens or chicken manure for the generation of biogas as alternative energy. Which allows to optimize resources. In the selection and design of the biodigester that adjusts to the conditions of the poultry farm, aspects such as the construction space, type of raw material, costs, maintenance, operation, performance and useful life are considered, necessary criteria that allow selecting and sizing the biodigester. biodigester.